Morris Water Maze and Contextual Fear Conditioning Tasks to Evaluate Cognitive Functions Associated With Adult Hippocampal Neurogenesis - Hernández-Mercado, Karina; Zepeda, Angélica (Frontiers in Neuroscience, 2022)
New neurons are continuously generated and functionally integrated into the dentate gyrus (DG) network during the adult lifespan of most mammals. The hippocampus is a crucial structure for spatial learning and memory, and the addition of new neurons into the DG circuitry of rodents seems to be a key element for these processes to occur. The Morris water maze (MWM) and contextual fear conditioning (CFC) are among the most commonly used behavioral tasks to study episodic-like learning and memory in rodents. However, the functional evaluation of adult hippocampal neurogenesis (AHN) through these paradigms has generated controversial findings. In this review, we analyze and discuss possible factors that could explain the inconsistent results among AHN studies; moreover, we provide specific suggestions for the design of more sensitive protocols to assess AHN-mediated learning and memory functions.